Sleep of Memory - Modiano, Patrick (The Margellos World Republic of Letters, 2018)
The newest best-seller by Patrick Modiano is a beautiful tapestry that brings together memory, esoteric encounters, and fragmented sensations Patrick Modiano's first book since his 2014 Nobel Prize revisits moments of the author's past to produce a spare yet moving reflection on the destructive underside of love, the dreams and follies of youth, the vagaries of memory, and the melancholy of loss.   Writing from the perspective of an older man, the narrator relives a key period in his life through his relationships with several enigmatic women-Geneviève, Martine, Madeleine, a certain Madame Huberson-in the process unearthing his troubled relationship with his parents, his unorthodox childhood, and the unsettled years of his youth that helped form the celebrated writer he would become. This is classic Modiano, utilizing his signature mix of autobiography and invention to create his most intriguing and intimate book yet